Structural and dynamical characterization of pRb, LTSV40 and the pRb-LTSV40 complex suggests a common mechanism for pRb inactivation - Padilla Franzotti, Carla Luciana; Palopoli, Nicolas; Palma, Juliana; Pierdominici-Sottile, Gustavo (Frontiers in Chemical Biology, 2025)
IntroductionThe retinoblastoma protein (pRb) is a key regulator of the cell cycle that suppresses cell proliferation by binding to E2F transcription factors. Disruption of this pathway, commonly through mutations or interactions with viral oncoproteins, can lead to uncontrolled cell growth and cancer. The large T antigen of simian virus 40 (LTSV40) is known to bind pRb, thereby inhibiting its interaction with E2F transcription factors. However, the structural and dynamic mechanisms underlying this inhibition remain incompletely understood.MethodsWe employed molecular dynamics (MD) simulations, principal component analysis, and cluster analysis to investigate the conformational dynamics of pRb, LTSV40, and their complex. Our study focused on an intrinsically disordered region on the C-terminal side of the LFCSE motif of LTSV40, referred to as Linker 1.ResultsOur simulations reveal that Linker 1 undergoes a significant conformational shift upon binding to pRb. While this region adopts a predominantly bent structure in the unbound state, it transitions into an extended conformation in the complex. As a consequence of this change, the C-terminal segment of LTSV40 obstructs access to the AB-cleft of pRb, the binding site for E2F.DiscussionOur findings suggest that the inactivation mechanism of pRb by LTSV40, as unveiled by MD simulations, could represent a broader strategy employed by other viral oncoproteins containing similar LXCXE motifs and adjacent disordered regions. This mechanism may even extend to endogenous pRb inactivation. As our conclusions are based on computational modeling, they require experimental validation. Such confirmation would pave the way for developing therapeutic strategies aimed at reactivating pRb function in pathologies where it is compromised.